Family physicians supporting patients with palliative care needs within the patient medical home in the community: an appreciative inquiry study - Amy Tan; Aynharan Sinnarajah; Ronald Spice (BMJ Open)
Objectives Canadians want to live and die in their home communities. Unfortunately, Canada has the highest proportion of deaths in acute care facilities as compared with other developed nations. This study aims to identify the essential components required to best support patients and families with palliative care needs in their communities to inform system changes and empower family physicians (FPs) in providing community-based palliative care for patients.Design Appreciative inquiry (AI) methodology with individual interviews. Interview transcripts were analysed iteratively for emerging themes and used to develop ‘possibility statements’ to frame discussion in subsequent focus groups. A conceptual framework emerged to describe the ‘destiny’ state as per AI methods.Setting FPs, palliative home care providers, patients and bereaved caregivers were recruited in the urban and surrounding rural health authority zones of Calgary, AB, Canada.Participants 9 females and 9 males FPs (range of practice years 2–42) in interviews; 8 bereaved caregivers, 1 patient, 26 palliative home care team members in focus groups. Interviews and focus groups were recorded digitally and transcribed with consent.Results The identified themes that transcended all three groups created the foundation for the conceptual framework. Enhanced communication and fostering team relationships between all care providers with the focus on the patient and caregivers was the cornerstone concept. The FP/patient relationship must be protected and encouraged by all care providers, while more system flexibility is needed to respond more effectively to patients. These concepts must exist in the context that patients and caregivers need more education regarding the benefits of palliative care, while increasing public discourse about mortality.Conclusions Key areas were identified for how the patient’s team can work together effectively to improve the patient and caregiver palliative care journey in the community with the cornerstone element of building on the trusting FP–patient longitudinal relationship.